Initial Report of Bloom of ichthyotoxic Karenia mikimotoi (Dinoflagellate sp) along the Coast of Ormara (Baluchistan) Pakistan - Tahira Naz,; Ghazala Siddique,; Zaib-Un-Nisa Burhan,; Pirzada Jamal Ahmed Siddique, (International Journal of Natural Sciences: Current and Future Research Trends, 2024)
A unique HAB event of a typical ichthyotoxic dinoflagellate species Karenia mikimotoi was observed during routine sampling in the month of October, 2009 from coast of Ormara (Baluchistan) Pakistan (Arabian Sea). The bloom appeared as rust brown appearance stretched over approximately a km of distance. Highest cell density 2.7×10 7 Cells/L was observed during microscopic counts, which is the highest cell concentration ever recorded.  This bloom was investigated for a period of three months; however the bloom was disappeared from the area and replaced by other members of microplankton community. The observed bloom also composed of other microplanktonic groups including dinoflagellates, diatoms and ciliates with various cell abundance. Among dinoflagellates, Triposfusus sp and Noctiluca scintillans were found in high abundance of 4×103 Cells/L, 1×103Cells/L, respectively. It is followed by five different species of Prorocentrum. Along with the bloom of Karenia mikimotoi 12 toxic species were also observed belonging to dinoflagellates and diatoms. The manifestation of Karenia mikimotoi bloom to the coastal waters of Pakistan could be an alarming situation and HAB prevention measurements should be taken to avoid the damage of ecosystem.